2021
DOI: 10.3390/scipharm90010003
|View full text |Cite
|
Sign up to set email alerts
|

The Development and the Validation of a Novel Dissolution Method of Favipiravir Film-Coated Tablets

Abstract: The aim of this study was to develop and validate a dissolution test for favipiravir release in a tablet dosage form using ultra-high performance liquid chromatography (UHPLC). The dissolution method was developed by testing the solubility of favipiravir in media with different pH values. The results demonstrated that the best dissolution was achieved in phosphate buffer with a pH of 6.8. The amount of favipiravir that was released was about 100% after 30 min. The UHPLC method presented linearity (R = 1.000) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…Because the results showed a better fit 36 , phosphate buffer medium (pH 6.8) is recommended as the optimal dissolution medium for level C IVIVC. These findings were consistent with results obtained by Göktuğ et al 37 who concluded that 900 mL of phosphate buffer (pH 6.8) maintained at 37.0±0.5°C is considered as proper dissolution medium for favipiravir tablets if using USP (apparatus II) at 50 rpm for 30 min. In vitro-in vivo correlations (IVIVCs) are generally practiced for modified-release (MR) formulations.…”
Section: Discussionsupporting
confidence: 92%
“…Because the results showed a better fit 36 , phosphate buffer medium (pH 6.8) is recommended as the optimal dissolution medium for level C IVIVC. These findings were consistent with results obtained by Göktuğ et al 37 who concluded that 900 mL of phosphate buffer (pH 6.8) maintained at 37.0±0.5°C is considered as proper dissolution medium for favipiravir tablets if using USP (apparatus II) at 50 rpm for 30 min. In vitro-in vivo correlations (IVIVCs) are generally practiced for modified-release (MR) formulations.…”
Section: Discussionsupporting
confidence: 92%
“…Exposes the UV-Vis spectra of FVP. The scanned range between 200 to 400nM and two absorption bands appeared at 221 and 325nM [45][46]. The obtained results were in good agreement with electrochemical impedance measurements of graphene and G/In 2 O 3 composites, which give a high surface area along with better electron conduction.…”
Section: Sample Preparationsupporting
confidence: 69%
“…The general procedure to develop a dissolution method includes (1) understanding the properties of drug substance and drug product, (2) evaluating sink conditions, (3) optimizing the dissolution conditions, and (4) evaluating the dissolution profiles and finalizing the method conditions [14][15][16][17][18][19][20][21]. One-factor-at-a-time (OFAT) approach is commonly used for process and method optimization [22,23].…”
Section: Introductionmentioning
confidence: 99%